Corporate Community Involvement to Manage Legitimacy: Noble but Quasi-Ethical - Ueno, Tomoka (2013)
This dissertation intends to explore the relationship between businesses and society, focusing on corporate community involvement (CCI) and legitimacy gained by businesses from their involvement in society. Social disclosures of two companies in the retail sector were examined in order to identify how the businesses manage their legitimacy through CCI. The analysis was guided by previous research by Castelló and Lozano (2011), who examined corporate sustainability reports and legitimacy. The findings of this dissertation are consistent with the previous research to the extent that both identified three types of rhetoric, namely strategic, institutional and dialectic, which have an orientation towards pragmatic, cognitive and moral legitimacy respectively. As a whole, social disclosure about CCI is assumed to reflect ‘noble’ attributes, whereby the companies try to present themselves as responsible, philanthropic and ethical entities rather than organisations who seek economic and non-economic returns from society. These noble attributes are leaning towards moral legitimacy; however, the results suggest that the companies’ efforts to manage this moral legitimacy is still at an embryonic stage, considering that how they promote a dialogue between the company and stakeholders as well as how they ensure stakeholder participation in businesses’ decision-making are not sufficiently communicated. This embryonic communicative approach may be indicative of the companies’ quasi-ethical attitudes, which might result in damage to their legitimacy.